Employing Local Ecological Knowledge to reveal interactions between artisanal fishers and Guiana Dolphins (Sotalia guianensis) along the Maranhão coast, northern Brazil - Filgueira, Carlos Henrique Marinho dos Santos; Vidal, Marcelo Derzi; Hauser-Davis, Rachel Ann; Siciliano, Salvatore (Ethnobiology and Conservation, 2025)
The Guiana dolphin (Sotalia guianensis) is a cetacean found in tropical coastal waters of the Western Atlantic, distributed from Honduras to northern Santa Catarina, Brazil. Its restricted distribution and interaction with human activities, such as artisanal fishing and pollution, make it highly vulnerable to anthropogenic threats, being classified as near threatened by the International Union for Conservation of Nature (IUCN) and vulnerable by the Brazilian Chico Mendes Institute for Biodiversity Conservation (ICMBio), the Brazilian Ministry of the Environment's administrative arm. Local Ecological Knowledge (LEK) is essential to understand interactions between fishing communities and this species. In this sense, this study aimed to identify the interactions between artisanal fishers and Guiana dolphins on the coast of Maranhão, aiming to provide relevant information on Guiana dolphins, essential to support conservation efforts for the species. A total of 88 semi-structured questionnaires were applied to fishers from the Tubarão Bay Extractive Reserve and São Marcos Bay, in Maranhão, northern Brazil. The calculated Smith's Salience Index revealed that the most valued ethnospecies are mullet, hake and croaker. Although overlaps between ethnospecies and the Guiana dolphin diet are noted, no direct conflicts were recorded. Some fishers perceive the presence of dolphins in a positive light, associating them with helping them locate fish, while others view the interaction negatively, considering that dolphins feed on fish caught in nets. Most fishers (56.8%) are not bothered by the presence of dolphins during fishing, and 82.95% stated that they do not interfere. Although 45.4% of fishers believe that dolphins can get entangled in fishing gear, there were no records of intentional captures. The importance of conservation and environmental education strategies is highlighted to ensure harmonious coexistence between fishers and Guiana dolphins.